Análise das propriedades de misturas asfálticas com pelete e agregados de resíduos de concreto - Marques, Vagner da Costa (2014)
This dissertation is included in area of reuse of solid wastes in paving, with objective to use recycled concrete aggregates and pellet in asphaltic surface course. The aim of the research was to analyze the technical feasibility of asphalt mixtures made with recycled concrete aggregates and pellet, in partial replacement of natural aggregates of the conventional asphalt mix, from tests of physical characterization of aggregates and mechanical performance of asphalt mixtures. The materials used were crushed stone 19 mm, crushed stone 12 mm, crusher dust, recycled concrete aggregate, pellet and 50/70 pen asphalt cement, these materials were obtained from companies in the state of Paraíba. For natural aggregates were performed grading, Los Angeles abrasion, absorption and density. For recycled concrete aggregates were made grading and specific density, and for pellet was carried out grading. One conventional asphaltic mixture were produced containing natural aggregates (crushed stone 19, crushed stone 12, crusher dust) and 50/70 pen asphalt cement, and five asphaltic mixtures were made with partial replacements of crusher dust for recycled concrete aggregates and pellet, in proportions: i) 25% of recycled concrete aggregates; ii) 2% of pellet; iii) 4% of pellet; iv) 23% of recycled concrete aggregates with 2% of pellet, and v) 21% of recycled concrete aggregates with 4% of pellet. The C grading envelope was used and chosen according to DNIT ES 031/2006. The mixtures were performed by the Marshall mix design. The mechanical tests performed were Marshall stability, tensile strength by diametric compression, resilient modulus and Lottman test. The hot asphalt mix containing 75% of natural aggregates, 23% of recycled concrete aggregates and 2% of pellet showed greatest number of parameters in accordance with the technical standards, as a result the best technical viability